The influence of Islam on Albanian culture - Shehu, Fatmir Mehdi (International Islamic University Malaysia, 2011)
This paper examines the influence of Islam on Albanian culture. The Islamization process of the Albanian culture was very crucial for the Albanians themselves as it gave them a new identity, which they lacked since their settlement on the Adriatic shores. According to history, Albanians, the biggest Muslim nation dwelling in the Balkans, South#East of Europe, are believed to be the descendents of the ancient Illyrians, who settled in Europe around 2500 years ago. They lived a social life based on tribalism, where every tribe had established its own cultural system and way of life. Thus, their cultural differences disallowed them to unite. Such situation did not change, even when Christianity was introduced to them. Because, Christianity came to Albania through two great dominations: Christian Catholics of Vatican (the Northern part of Albanian) and Christian Orthodox of Greece (the Southern part of Albania). The continuous religious and political suppression faced by the Albanians from their Byzantine and Latin masters enabled them to be the first people of the Balkans, who welcomed openheartedly the Ottoman Muslims and embraced Islam as their new way of life in the 15th century. The study focuses on the following issues: (1) Historical background of Albania and Albanians; (2) The genesis of Albanian culture; and (3) The process of integration between Islamic culture and Albanian culture. This research attempts to provide important findings, which will be very helpful to the Muslims and others.